2008
DOI: 10.1111/j.1559-1816.2008.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Information Regarding Social‐Sexual Behavior as an Antecedent to Perceptions of Ineffectiveness in the Workplace1

Abstract: Three experimental studies investigated whether information implying social‐sexual behavior (any non‐work‐related behavior containing a sexual component) by employees would influence judgments of their effectiveness. In managerial and entry‐level positions, both male and female employees depicted as engaging in social‐sexual behaviors at work were perceived as less effective and less desirable as bosses, compared to identically described managers for whom no social‐sexual behavior information was provided. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For example, research indicates that involvement with a married coworker is correlated with perceptions of decreased competence (Brown & Allgeier, ). Liberman and Okimoto's () research similarly reveals that managers depicted as engaging in social‐sexual behaviors with employees are perceived as less desirable and less effective as bosses compared to identically described managers for whom no social‐sexual behavior information is provided.…”
Section: Domains Of Coworker Evaluation As Antecedents To Differing Wmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, research indicates that involvement with a married coworker is correlated with perceptions of decreased competence (Brown & Allgeier, ). Liberman and Okimoto's () research similarly reveals that managers depicted as engaging in social‐sexual behaviors with employees are perceived as less desirable and less effective as bosses compared to identically described managers for whom no social‐sexual behavior information is provided.…”
Section: Domains Of Coworker Evaluation As Antecedents To Differing Wmentioning
confidence: 98%
“…Through a halo effect, this may lead to indirect negative perceptions and evaluations as well. For example, ceteris paribus, perceived romantic involvement with underlings has been shown to lead to more negative evaluations of managerial performance and effectiveness (Liberman & Okimoto, ).…”
Section: Domains Of Coworker Evaluation As Antecedents To Differing Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, Liberman and Okimoto (2008) showed that observers do indeed perceive employees who engage in social-sexual behaviors to be less effective than identically competent employees not behaving in such a manner. Social-sexual behaviors, or nonwork-relevant behaviors at work that contain a sexual component, include the act of being in a WR (Liberman & Okimoto, 2008). Engaging in an HWR thus may hinder individuals’ careers, regardless of whether there are differences in qualification between these individuals and those who are not in a romantic liaison with their superiors.…”
Section: Overview Of Hwr Researchmentioning
confidence: 99%
“…Most empirical studies on workplace romance (e.g., Anderson & Fisher, 1991;Brown & Allgeier, 1996;Horan & Chory, 2011;Mainiero, 1986;Powell, 2001;Quinn, 1977) have relied mainly on data from co-workers' observations and self-report surveys (Wilson, 2015), which can provide useful knowledge on organization morale and equitable employee treatment (Cowan & Horan, 2014;Liberman & Okimoto, 2008;Pierce & Aguinis, 2009). However, it is also important to conduct interviews and discussions with people who have experienced workplace romance to supplement the largely third-person perspective of previous research with first-person perceptions.…”
Section: Summary and Aimmentioning
confidence: 99%